Multiscale deformations lead to high toughness and circularly polarized emission in helical nacre-like fibres - Jia Zhang (Nature Portfolio, 2016)
The mechanical properties and hierarchical structure of nacre have been widely investigated as a biomimetic template for applications. Here, the authors demonstrate that nacre-like fibres made from nanoplatelets and polymers show exceptional stretchability and toughness.